The collection of Sri Lankan freshwater fishes reported on by Pieter Bleeker (1863) (Osteichthyes: Cyprinidae, Danionidae, Nemacheilidae) - Sudasinghe, Hiranya; Kottelat, Maurice; Pethiyagoda, Rohan (Zootaxa, 2025)
The whereabouts of the types of the six species of Sri Lankan cypriniform fishes described by Pieter Bleeker in 1863 have long remained unknown. These specimens are now reported from the collection of the Naturalis Biodiversity Centre in Leiden, the Netherlands. Here we provide meristic and morphometric data on (as well as photographs of) the type specimens in this collection. These include the three syntypes of Garra ceylonensis, the holotype of Systomus pleurotaenia, the holotype of Devario micronema, one of the three syntypes of Devario lineolatus, and the three syntypes of Schistura notostigma. The five syntypes of Plesiopuntius bimaculatus, though present, are in a very poor state. Devario lineolatus (Bleeker), for which the replacement name D. monticola has previously been proposed, is a junior subjective synonym of D. malabaricus (Jerdon). Devario micronema is the species that occurs in the lowlands of south-western Sri Lanka. An examination of the three syntypes of Schistura notostigma shows it to be distinct from S. madhavai and S. scripta.